2017
DOI: 10.5539/ijc.v9n4p22
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Friendly and Cheap Removal of Lead (II) and Zinc (II) from Wastewater with Fish Scales Waste Remains

Abstract: In this article, the physical and chemical properties of pulverized, vinegar treated waste from fish scale remains of fish from Lake Ngami in Sehitwa near Maun, Botswana, were investigated for a possibility of being employed as an environmentally friendly and cheap sorbent material for reducing or removing excess, toxic, heavy metal ions from wastewater before different uses. Lead (II) and Zinc (II) ions were selected as model ions to demonstrate the potential of fish scale waste remains in removing excess tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…6). Similar reports about shift in peaks were given by many workers 17–21 . The phosphate and sulphonate peaks completely disappeared in the treated biosorbent spectrum.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…6). Similar reports about shift in peaks were given by many workers 17–21 . The phosphate and sulphonate peaks completely disappeared in the treated biosorbent spectrum.…”
Section: Resultssupporting
confidence: 88%
“…Similar reports about shift in peaks were given by many workers. [17][18][19][20][21] The phosphate and sulphonate peaks completely disappeared in the treated biosorbent spectrum. In the present work, the functional groups of interest involved in the adsorption process were carboxyl and amino groups due to their valence charge; however, phosphate and sulphonate groups also are important because they perform complexation with pollutant ions process during treatment.…”
Section: Ftir Analysismentioning
confidence: 99%
“…In this study, the peaks that correspond to frequencies of vibration showed visible shift in their peak positions after adsorption treatment with effluent samples. Dried fish scale adsorbent and fish scale biochar exhibited sharp peaks at 547, 570, 601, 1010, and 1018.41 cm −1 which corresponds to the presence of functional groups such as triple bending vibrations of phosphate, alkane, carbonate, and carboxyl groups 34–37 . The spectrum of control adsorbent showed peaks at 493, 686, 1049, and 3495 cm −1 which indicates the presence of CH aromatic, amide (NH), CO stretching, and OH stretching mode of hydroxyl functional groups 38–42 .…”
Section: Resultsmentioning
confidence: 99%
“…The fish scales waste from Tilapia ruweti (Tr) sampled at Lake Ngami in Sehithwa near Maun, Botswana were treated and characterized following an adapted method by Stevens and Batlokwa [21]. The scales were sun dried for 2 days and pulverized using a Fritsch pulverisette 5 pulverizer obtained from Fritsch (Berlin, Germany), then sieved to 63 -200-micron mesh size.…”
Section: Tilapia Ruweti Scales Remain Valorization and Characterizationmentioning
confidence: 99%
“…Afterwards, a face centered central composite design was then conducted to determine the optimum conditions for each factor, resulting to a maximized response of the experiments. During the screening process, the experimental conditions in Table 1 were adapted [21]. The resulting filtered solution was transferred into a 50 mL volumetric flask and the sample diluted with deionized water up to the mark.…”
Section: Optimization Of Adsorptive Parametersmentioning
confidence: 99%